Pengujian Black Box Aplikasi Pendataan Buku Perpustakaan SDN Larangan 04 - Tri Widiayu Ningsih; Ridwan Hakim; Satria Anggara Fayyadh Alwaly; Arich Herdiansyah; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Book data collection application in the SDN Larangan 04 library is an application that is used to record the availability of books, borrow books and also return books to the library. If an error occurs in the application it will cause an error which will make the library admin have to record it manually by writing in the ledger. To determine the level of quality, it is necessary to test the application. At the testing stage that will be tested are specifications, designs, and also coding using the Black Box method. The Black Box testing method is carried out to find out software errors related to inappropriate functions or errors in each interface display or data structure in an external database, sub-optimal work processes, and also errors when initializing or terminating. The end result of software testing is that it is free from errors that will hinder the user from completing his task. And informs that the software meets the specifications that have been previously determined.